2016
DOI: 10.1021/acs.inorgchem.6b00667
|View full text |Cite
|
Sign up to set email alerts
|

Group 14 Dithienometallole-Linked Ethynylene-Conjugated Porphyrin Dimers

Abstract: The considerably conjugated π systems of the group 14 dithienometallole-linked ethynylene-conjugated porphyrin dimers (1Ms) were described based on comprehensive experimental and theoretical studies. The electronic absorption spectra of 1M displayed a large splitting in the Soret band and a red-shifted Q-band, indicating that the dithienometallole spacer was effective in facilitating the porphyrin-porphyrin electronic coupling. Torsional planarization behaviors of 1M were observed in the time-resolved fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…The spectroscopic signatures of 2 were somewhat broadened in C 6 H 12 (Figure 5) as well as in n-hexane, toluene, tetrahydrofuran, and dichloromethane as shown in our previous report. 27 Upon the addition of C 6 F 6 , 2 showed unequivocal spectral sharpening and a bathochromic shift (Figure 5A). The spectral changes through several isosbestic points indicate a two-state equilibrium.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The spectroscopic signatures of 2 were somewhat broadened in C 6 H 12 (Figure 5) as well as in n-hexane, toluene, tetrahydrofuran, and dichloromethane as shown in our previous report. 27 Upon the addition of C 6 F 6 , 2 showed unequivocal spectral sharpening and a bathochromic shift (Figure 5A). The spectral changes through several isosbestic points indicate a two-state equilibrium.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…This study employed highly soluble porphyrin 1 bearing two 3,4,5-tri((S)-3,7-dimethyloctyloxy)phenyl groups at the meso-positions, which adopted the form of sticky liquid at ambient temperature under the solvent-free conditions, 25,26 and the dithienosilole-linked dimer 2, whose spectroscopic signature was susceptible to the torsional conformations due to the freely rotatable ethynylene linkages (Chart 1). 27…”
Section: ■ Introductionmentioning
confidence: 99%
“…This approach was proposed by Anderson and co-workers using a 9,10-anthracene-bridged ethynyl-conjugated porphyrin dimer for the first time 57 59 and has been reported for other aryl-bridges such as thiophene, 57 59 pentacene, 60 benzobisthiadiazole, 60 dimethylthiadiazoloquinoxaline, 61 and dithienometallole. 62 However, further extension to an alternating anthracene–porphyrin polymer has not been conducted. Along with the study of porphyrin glass, we recently reported an alternating anthracene–porphyrin polymer 1 ( M n = 54 000, M w / M n = 4.2, T g = 94 °C) that formed a metal-lustrous self-standing film, “porphyrin foil” ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most efficient π-conjugations of aryl-bridged ethynyl-conjugated porphyrin dimers has been achieved by a possible resonance between a benzenoid–acetylene and quinoidal–cumulenic conjugation. This approach was proposed by Anderson and co-workers using a 9,10-anthracene-bridged ethynyl-conjugated porphyrin dimer for the first time and has been reported for other aryl-bridges such as thiophene, pentacene, benzobisthiadiazole, dimethylthiadiazoloquinoxaline, and dithienometallole . However, further extension to an alternating anthracene–porphyrin polymer has not been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we intend to design small‐bandgap conjugated polymers based on porphyrin units with quinoid motif. The idea was initiated from the studies that conjugated molecules based on porphyrin with ethylnyl linkers show quinoid properties . In addition, porphyrin as a strong electron‐donating unit has been widely used to design NIR conjugated material via donor–acceptor design .…”
mentioning
confidence: 99%